Bandar Bagan Datuk, Perak: reviving pekan koboi as a historic town center - Khairuddin, Nurul Azriana; Mansor, Mazlina; Ab Sani, Jasasikin (IIUM Press, 2024)
Known as Pekan Koboi by the locals, and it is planned to be developed as a dynamic historic living city. The purpose of this research is to revitalise Bagan Datuk town as a dynamic historic living town centre, with three objectives: 1) to integrate the identity of Bagan Datuk District, 2) to introduce a contemporary living grounded in commerce activities, and 3) to promote sustainable living through smart energy solutions. Among the issues concerning the town are its historical value and identity, potential as a tourism transit, valuable estuary, unappealing and isolated spaces, and security design considerations. The presence of semi-residential, administrative, and public spaces becomes elements of a dynamic living town capable of accepting contemporary approaches without jeopardising its historical built fabric.